Meso-optics : foundations and applications - Soroko, L. M. (World Scientific, 1996)
The monograph covers various meso-optical elements, diffraction free light beams, localized electromagnetic fields, gravitational lens, meso-optical devices for transportation of the synchrotron radiation, meso-optical microscopes for high energy elementary particle physics, and the history of meso-optics. Some integral transforms useful in meso-optics are presented in the Appendix. The author is an active participant of many investigations in meso-optics and provides an up-to-date encyclopedic review of the theoretical and experimental investigations on Meso-Optics (optics of the conical wave fields).
Keywords: Fourier transform optics.; Head waves.; Coherence (Optics); elektronické knihy; electronic books